Barriers and Facilitators to Exercise Participation Among Frail Older African American Assisted Living Residents. (March 2021) - Bender, Alexis A.; Halpin, Sean N.; Kemp, Candace L.; Perkins, Molly M.
Despite the well-known health benefits of physical activity, older adults are more sedentary than any other age group. This issue is particularly true for assisted living (AL) residents, which also represents an important and often overlooked aspect of palliative care. Here, we analyze ethnographic and interview data from a longitudinal study aimed at identifying best practices for palliative care in one African American AL community. The aim was to identify the factors that facilitate and constrain resident participation in instructor-led group exercise. Thematic analysis identified several main themes including the quality and location of the exercise program, AL staffing limitations, residents' health and function, values about exercise, and residents' interest in recreation and social engagement. We identified facilitators and barriers that shaped residents' opportunity, desire, and commitment related to attending group exercise. Findings have implications for interventions aimed at increasing resident participation in group exercise, leading to multiple health benefits.